AKUNTANSI SYARIAH: PENDEKATAN SEJARAH - Hasnidar Hasnidar (JURNAL AKUNTANSI BARELANG, 2019)
The birth of shariah accounting paradigm can not be separated from the factors of development of Islamic economic discourse and sharia financial system that began to emerge since the mid-1990s. For some, shari'ah accounting is something that is "forced". This assumption is neither misleading nor true, since shari'a accounting has a strong historical roots in Islamic civilization long before Western civilization reached its golden peak until today. The existence of Islamic civilization that lasted for 600-1300 AD, where the progress of Islamic science reached its peak of the year 900-1200 M. Recording procedure has begun to be practiced since the Caliph Umar Bin Khattab, ie in the period 14-24 H (636-645 M). At this time Baitul Mal requires formal recording of funds obtained by institutions from various sources.